Transformational Leadership and Its Impact on School Performance in the 21st Century - Haryanengsi; Radiana, Usman (Universitas Negeri Jakarta, 2024)
Background Transformational leadership has emerged as a critical factor in shaping school performance in the dynamic and complex educational environment of the 21st century. Purpose This study explores the influence of transformational leadership on various dimensions of school performance, including academic outcomes, teacher motivation, and institutional innovation. Design/method/approach Utilizing a comprehensive literature review and empirical data from multiple educational institutions, this article examines the mechanisms through which transformational leadership fosters a collaborative, motivated, and performance-driven school culture. Results Key leadership components—such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—are analyzed in relation to their impact on both teachers and students. The findings suggest that schools led by transformational leaders experience higher levels of teacher engagement, improved student outcomes, and greater adaptability to educational reforms. Contribution/value This paper contributes to the growing body of research on educational leadership by highlighting the critical role of transformational leadership in driving school success in the modern era.